Nausea - Sartre, Jean-Paul, 1905-1980 (A New Directions paperbook, 2007)
French writer who is horrified at his own existence. In impressionistic, diary form he ruthlessly catalogues his every feeling and sensation. His thoughts culminate in a pervasive, overpowering feeling of nausea which "spreads at the bottom of the viscous puddle, at the bottom of our time the time of purple suspenders and broken chair seats. Roquentin's efforts to come to terms with life, his philosophical and psychological struggles, give Sartre the opportunity to dramatize the tenets of his Existentialist creed.